2018
DOI: 10.14814/phy2.13611
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of maximal mitochondrial oxidative phosphorylation in permeabilized fibers from thevastus lateralisemploying high-resolution respirometry

Abstract: The purpose was to assess the impact of various factors on methodological errors associated with measurement of maximal oxidative phosphorylation (OXPHOS) in human skeletal muscle determined by high‐resolution respirometry in saponin‐permeabilized fibers. Biopsies were collected from 25 men to assess differences in OXPHOS between two muscle bundles and to assess the correlation between OXPHOS and the wet weight of the muscle bundle. Biopsies from left and right thighs of another five subjects were collected on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 17 publications
4
30
3
Order By: Relevance
“…Permeabilized fibre preparation was conducted as published elsewhere . Briefly, a second portion of the muscle biopsy (~5 mg wet weight) was immediately transferred into ice‐cold relaxing medium (BIOPS) containing 10 mmol L −1 Ca 2+ /EGTA buffer, 20 mmol·L −1 imidazole, 50 mmol·L −1 K + ‐4‐morpholinoethanesulfonic acid (Mes), 0.5 mmol·L −1 dithiothreitol, 6.56 mmol·L −1 MgCl 2 , 5.77 mmol·L −1 ATP and 15 mmol·L −1 phosphocreatine at pH 7.1.…”
Section: Methodsmentioning
confidence: 99%
“…Permeabilized fibre preparation was conducted as published elsewhere . Briefly, a second portion of the muscle biopsy (~5 mg wet weight) was immediately transferred into ice‐cold relaxing medium (BIOPS) containing 10 mmol L −1 Ca 2+ /EGTA buffer, 20 mmol·L −1 imidazole, 50 mmol·L −1 K + ‐4‐morpholinoethanesulfonic acid (Mes), 0.5 mmol·L −1 dithiothreitol, 6.56 mmol·L −1 MgCl 2 , 5.77 mmol·L −1 ATP and 15 mmol·L −1 phosphocreatine at pH 7.1.…”
Section: Methodsmentioning
confidence: 99%
“…17 Mitochondrial respiration values, as well as improvements in mitochondrial respiration following exercise training are also quite variable between studies. 3,10,14,16,18,19 For example, Irving et al 18 observed a ~1.5-fold change in mitochondrial respiration after moderate intensity endurance training (n = 34), while Robach et al 20 did not observe any change after a similar intervention (n = 17). Mitochondrial respiration capacity in human exercise intervention studies is not exclusive to skeletal muscle samples.…”
Section: Introductionmentioning
confidence: 99%
“…2 Mitochondrial respiration measured by maximal oxygen consumption in skeletal muscle fibers, is currently the primary way of assessing mitochondrial capacity. 3,4 The most common method in human skeletal muscle uses fibers permeabilized by saponin. 5,6 Using a combination of different substrates, this technique is able to mimic the processes (ie, TCA cycle and ETS) occurring within the mitochondrion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When isolated mitochondria are evaluated, large amounts of tissue are needed [13][14][15][16]. The preparation of permeabilised muscle fibres is manually demanding and results can be operator-dependent [17,18].…”
Section: Introductionmentioning
confidence: 99%